Authority without identity: defending advance directives via posthumous rights over one's body. Issue 4 (22nd December 2018) - Persad, Govind
Abstract : This paper takes a novel approach to the active bioethical debate over whether advance medical directives have moral authority in dementia cases. Many have assumed that advance directives would lack moral authority if dementia truly produced a complete discontinuity in personal identity, such that the predementia individual is a separate individual from the postdementia individual. I argue that even if dementia were to undermine personal identity, the continuity of the body and the predementia individual's rights over that body can support the moral authority of advance directives. I propose that the predementia individual retains posthumous rights over her body that she acquired through historical embodiment in that body, and further argue that claims grounded in historical embodiment can sometimes override or exclude moral claims grounded in current embodiment. I close by considering how advance directives grounded in historical embodiment might be employed in practice and what they would and would not justify.